Analisis Verba Transitif dan Intransitif dalam Cerita Pendek “Al-Athfal Wa Al-Qiro’ah” - Malida, Alya (Crises on Languages and Literature, 2024)
In terms of syntax, verbs can be distributed together with other grammatical units so that a verb distribution is formed that can become the core element of a phrase. There are several subcategories for verbs. Predicate verbs in Indonesian can be divided into two types, namely intransitive verbs and transitive verbs. This study aims to determine whether these verbs are used by the rules of Arabic grammar (syntax). This research method uses a qualitative descriptive analysis method. The data collection technique in this study is by reading and recording. The data source is in the short story "Al-Athfal wa al-qiroah" in the book al'arabiyah baina yadaik. This study uses a repeated reading method in a short story, "Al-Athfal wa al-qiroah," in Al'Arabiyah Baina Yadaik. After data collection, the next step is to identify the type of verb based on the need for the object. The main categories are transitive and intransitive verbs, each with specific criteria. Analysis is carried out on the verbs; the results are recorded and discussed. Next, conclusions are drawn after analyzing the possibility of syntactic errors based on the transitive or intransitive nature of the verbs in the data. The results of the study found 15 transitive and intransitive verb data. Of these, 9 are transitive verb data, and 6 are intransitive verb data. The study results show no errors in language structure, especially related to transitive and intransitive verbs, and indicate that the story's author has good syntactic skills in Arabic.